Massa Medicata Fermentata treated spleen deficiency constipation by mediating intestinal microbiota and serum peptide - Guo, Kangxiao; Tang, Yuan; Yang, Tao; Yan, Yongwang (Frontiers in Cellular and Infection Microbiology, 2025)
ObjectivesTo investigate the correlation between the treatment of spleen deficiency constipation and the typical brain and intestinal peptides.MethodsA total of 18 male Kunming mice were randomly divided into three treatment groups (n = 6): normal group (CC), model group (CM), and Massa Medicata Fermentata intervention group (CG). CM and CG were used to establish a spleen deficiency constipation mouse model. After the model was finished, CG was infused with 0.15 g/mL Massa Medicata Fermentata water infusion at a dose of 4 g/(kg·day), twice a day, at 0.4 mL. An equal amount of distilled water was infused in CC and CM for 7 days. The body weight and fecal water content of the mice were monitored during the modeling. Following the intervention, 16S rRNA amplicon sequencing was used to analyze changes in the microflora in the intestinal contents, and serum substance P (SP), vasoactive intestinal peptide (VIP), and calcitonin gene-related peptide (CGRP) levels were determined via ELISA.ResultsThe modeling had no significant effect on the weight of the mice, the water content of the mice’s feces was greatly reduced, and the feces were dry and hard. Constipation caused by spleen deficiency can lead to a decrease in serum SP and an increase in VIP and CGRP. After treatment with Massa Medicata Fermentata, SP, VIP, and CGRP all changed. Intestinal microbiota diversity of mice with spleen deficiency constipation, and the dominant microbiota and characteristic microbiota changed, indicating that the intestinal microbiota was unbalanced. After the intervention of Massa Medicata Fermentata, the intestinal microbiota diversity of spleen deficiency constipation mice increased; the dominant microbiota became Candidatus Arthromitus, Lactobacillus, unclassified Bacilli, Bacillus, Ligilactobacillus, Muribaculaceae, Bacteroides, and Enterorhabdus; and the characteristic microbiota became Candidatus Arthromitus. Through the analysis of characteristic microbiota and serum SP, VIP, and CGRP levels, Ligilactobacillus was found to be positively correlated with SP and negatively correlated with VIP, Akkermansia and Streptococcus were negatively correlated with SP, Candidatus Arthromitus was negatively correlated with CGRP, Akkermansia and Candidatus Arthromitus were negatively correlated with VIP, and Candidatus Arthromitus was negatively correlated with CGRP.ConclusionsMassa Medicata Fermentata can affect the secretion of short-chain fatty acids in the intestine by altering the microecological environment of the intestine, then affect the secretion of serum peptides in mice, and alleviate the spleen deficiency constipation.